Comparison of high-flow nasal oxygen therapy and non-invasive ventilation in ICU patients with acute respiratory failure and a do-not-intubate orders: a multicentre prospective study OXYPAL. Issue 2 (12th February 2021) - Robert, René; Frasca, Denis; Badin, Julie; Girault, C; Guitton, Christophe; Djibre, Michel; Beuret, Pascal; Reignier, Jean; Benzekri-Llefevre, Dalila; Demiri, Suela; Rahmani, Hassène; Argaud, Laurent Argaud; et al.
Abstract : Introduction: A palliative approach to intensive care unit (ICU) patients with acute respiratory failure and a do-not-intubate order corresponds to a poorly evaluated target for non-invasive oxygenation treatments. Survival alone should not be the only target; it also matters to avoid discomfort and to restore the patient's quality of life. We aim to conduct a prospective multicentre observational study to analyse clinical practices and their impact on outcomes of palliative high-flow nasal oxygen therapy (HFOT) and non-invasive ventilation (NIV) in ICU patients with do-not-intubate orders. Methods and analysis: This is an investigator-initiated, multicentre prospective observational cohort study comparing the three following strategies of oxygenation: HFOT alone, NIV alternating with HFOT and NIV alternating with standard oxygen in patients admitted in the ICU for acute respiratory failure with a do-not-intubate order. The primary outcome is the hospital survival within 14 days after ICU admission in patients weaned from NIV and HFOT. The sample size was estimated at a minimum of 330 patients divided into three groups according to the oxygenation strategy applied. The analysis takes into account confounding factors by modelling a propensity score. Ethics and dissemination: The study has been approved by the ethics committee and patients will be included after informed consent. The results will be submitted for publication in peer-reviewed journals. Trial registration number: NCT03673631